Pengembangan Sistem Informasi Tukar Barang Untuk Pemanfaatan Barang Tidak Terpakai dengan Flutter Framework - Sulaeman Santoso; Daniel Jahja Surjawan; Erico Darmawan Handoyo (Maranatha University Press, 2020)
Humans in general can not be separated from the consumptive lifestyle. Problems related to ownership of goods that are no longer in use are increasing. These items are stored and never used again by the owner. Most of these items do not have high sales value because of the condition of used goods or for some people the goods are unused. The item can be valuable in the hands of those who need it. Problem occur when information on the unused item does not reach to the person in need. This research attempt to develop an exchanging unused goods system without a payment process. Each item will be worth one token, this is done to prevent system exploitation, this differentiate the proposed system with other bartering system. Furthermore, the system was developed to be a portal in providing information and facilitating people who will barter their goods that are not used. For the process of giving and taking goods will be done separately